Implementation of RCM II (Reliability Centered Maintenance) and RPN (Risk Priority Number) in Risk Assessment and Scheduling Maintenance Task at HPB (High Pressure Boiler) Base On JSA (Job Safety Analysis) (Case study at PT. SMART Tbk. Surabaya) - Rachmad Tri Sulistiyono; Anda Iviana Juniani; Iva Setyana (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2008)
The operational of High pressure boiler (HPB) in industry has potential to result accident that is blow up. SMART Corp. Surabaya which is produce palm oil & margarine has operated HPB to support production process in Refinery & Fractionation unit. Production capacity of HPB is 1500 kkal with work pressure until 70 bar and 2900C temperature. One of the efforts to minimize risk consequences of HPB operation is by given maintenance. In case, to schedule maintenance task precisely is required failure and risk assessment to all possibility of functional failure of equipment. This assessment has not been done by maintenance division of SMART Corp yet. Hence, This research have study how to schedule maintenance task at HPB by apply RCM II method and RPN (Risk Priority Number) in risk assessment. Quantitative assessment is considered to decide preventive maintenance intervals by examine Maintenance cost (CM) and Repair cost (CR). JSA will observe potential hazard of maintenance task which have been scheduled at HPB.From the research result, have been known that there are 25 failure modes which follow functional failure of HPB operation. To anticipate failure modes of HPB operation, schedulemaintenance which have given by heed RCM II decision diagram are schedule on condition task, scheduled discard task, scheduled restoration task, and Combination of task. Preventive maintenance interval determinate at schedule discard & restoration task to expect that activities are technically feasible to reduce failure consequences of HPB equipment failure modes. By means of risk assessment with preventive maintenance interval consideration and also assessment at potential hazard maintenance task in JSA are expected to help increase effectiveness of maintenance task has been scheduled